Kredibilitas Komunikator pada Platform YouTube dengan Konten Misteri - Ferina, Sheren; Sari, Wulan Purnama (Prologia, 2025)
The horror and mystery genre are very popular in Indonesia, both in the form of films and digital content. Reporting from Radio Republik Indonesia, 10 of the 15 best-selling films in Indonesia as of 2023 are horror films. The development of social media has allowed anyone to become a communicator on social media. One of the famous mystery content creators on YouTube is Nessie Judge. This research aims to analyze Nessie Judge's credibility as a communicator on YouTube. This research uses a quantitative approach with descriptive statistical data processing techniques to see the audience's perception of Nessie Judge's credibility. The sampling technique used was simple random sampling (SRS) of 100 respondents using the Lemeshow formula. The research results show that the majority of respondents agree with Nessie Judge's statement as a credible communicator. Nessie Judge is considered to have in-depth knowledge, is trustworthy and consistent in her content, and has a communication style that is attractive to her audience. Then the results of the mean test show that the highest average value is in the attractiveness dimension and the lowest average value is in the trustworthiness dimension. It can be concluded that the results of the analysis show that Nessie Judge is considered a credible communicator as measured by the aspects of expertise, trustworthiness and attractiveness. Genre horor dan misteri merupakan salah satu genre yang ramai diminati di Indonesia, baik dalam bentuk film maupun konten digital. Dilansir dari Radio Republik Indonesia, 10 dari 15 film terlaris di Indonesia per 2023 merupakan film horor. Perkembangan media sosial telah mengizinkan siapapun untuk menjadi komunikator di media sosial. Salah satu kreator konten misteri yang terkenal di YouTube adalah Nessie Judge. Penelitian ini bertujuan untuk menganalisis kredibilitas Nessie Judge sebagai komunikator di YouTube. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik pengolahan data statistik deskriptif untuk melihat persepsi audiens terhadap kredibilitas Nessie Judge. Teknik sampling yang digunakan adalah simple random sampling (SRS) sebanyak 100 responden melalui rumus Lemeshow. Hasil penelitian menunjukkan mayoritas responden setuju dengan pernyataan Nessie Judge sebagai komunikator yang kredibel. Nessie Judge dinilai memiliki pengetahuan yang mendalam, terpercaya dan konsisten dalam kontennya, dan memiliki gaya komunikasi yang menarik oleh penontonnya. Kemudian hasil uji mean menunjukkan nilai rata-rata tertinggi terdapat pada dimensi daya tarik dan nilai rata-rata terendah terdapat pada dimensi keterpercayaan. Dapat disimpulkan bahwa hasil analisis menunjukkan Nessie Judge telah dianggap sebagai komunikator yang kredibel diukur dari aspek keahlian, keterpercayaan, dan daya tarik.